Conducting a Statewide Health Examination Survey: The Arkansas Cardiovascular Health Examination Survey (ARCHES) - Namvar Zohoori, MD, MPH, PhD; LeaVonne Pulley, PhD; Camille Jones, MD, MPH; John Senner, PhD; Hylan Shoob, PhD; Robert K. Merritt, MA (Centers for Disease Control and Prevention, 2011)
IntroductionThe Arkansas Cardiovascular Health Examination Survey is a health and nutrition examination survey designed to serve as a demonstration project for collection of data on the prevalence of chronic diseases and their risk factors at the state level. The survey was conducted from mid-2006 through early 2008.MethodsWe chose a cross-sectional representative sample of adult residents in Arkansas by using a 3-stage, cluster sample design. Trained interviewers conducted interviews and examinations in respondents' homes, collecting data on risk factors and diseases, blood pressure and anthropometric measurements, and blood and urine samples for analysis and storage. Food frequency questionnaires provided dietary and nutrient intake data. We accomplished the project using a collaborative model among several programs and partners within the state.ResultsA total of 4,894 eligible households were contacted by telephone. Of these, refusals accounted for 2,748, and 2,146 gave initial consent to participate, for an initial response rate of 44%. The final number of completed household visits was 1,385, resulting in a final response rate of 28.3%.ConclusionThe Arkansas Cardiovascular Health Examination Survey is among the first state-level health and nutrition examination surveys to be conducted in the United States. By using a collaborative model and leveraging federal funds, we engaged several partners who provided additional resources to complete the project. The survey provides the state with valuable state-level data and information for program design and delivery.